International Conference “Geometry, Topology, and Applications” - A. Garber; H. Edelsbrunner; A. Ivanov; O. Musin; M. Nevskii (Моделирование и анализ информационных систем)
The International Conference on “Geometry, Topology, and Applications”, dedicated to the upcoming 70th birthday of Nikolai Dolbilin, was organized by the International Delaunay Laboratory on Discrete and Computational Geometry and took place in September 23–27, 2013, at the P.G. Demidov Yaroslavl State University. This note highlights the main results presented at the conference and underlines the role of such meetings in the development of the field of Discrete and Computational Geometry in Russia.The article is published in the author’s wording.